Cost of respiratory syncytial virus hospitalisation in Brazilian infants: a micro-costing study from the perspective of a Brazilian tertiary public hospital, 2020–2023 - Nancy Oliveira dos Santos; Solange Batista da Silva; Edgard Joseph Kiriyama; Caroline Pimenta Nunes; Luís Felipe Batista Hiar; Leonardo Henrique Fiuza de Meireles; Francisco Neves Pereira; Ancelmo Honorato Ferraz de Sousa; Lital Moro Bass; Adriana Cristina D’Ornelas; Carla Souza Behr Pitoli; Rodrigo Fernandes Alexandre; et al. (BMC Public Health)
Abstract Background Respiratory Syncytial Virus (RSV) is the leading cause of hospitalisation for respiratory diseases among young children. Costing studies are essential for planning prevention strategies. Additional costing studies in middle-income countries (MIC) are still needed to understand the impact of hospitalisations given the high economic burden of RSV in these countries. We aimed to identify and quantify the resources required and associated costs of paediatric RSV hospitalisations at a tertiary hospital in a MIC. Methods A retrospective micro-costing study of RSV-related hospitalisations among children under the age of one year, from January 2020 to November 2023, was conducted at a tertiary public hospital in Brazil. Only cases of RSV isolated on molecular respiratory panel tests were eligible for inclusion. The study used direct and indirect expenses to calculate the average cost (AC) per hospitalisation, AC per hospital day, and the total financial impact of RSV-related hospitalisations using the absorption model. The analysis was clustered by age group and the necessity of intensive care admission. Financial data is presented in Brazilian reais (BRL) and United States dollars using purchasing power parity (USD-PPP). Results After excluding 1,354 positive tests (i.e., individuals aged one year or older), we included 231 hospital admissions. Of these, 83.1% required intensive care support. The AC per hospitalisation was BRL$29,285.47 (USD-PPP$12,051.63), with an average length of stay of 8.51 days, equivalent to BRL$3,801.00 (USD-PPP$1,564.19) AC cost per day. A total of 1,965 hospital days were counted, resulting in the financial impact at BRL$6.76 million (USD-PPP$2.78 million) due to RSV-related hospitalisations of infants in the study period. Hospitalisation episodes with intensive care unit admission were significantly more expensive, with the higher costs concentrated in the younger group (< 2 months old). Conclusions RSV-related hospitalisations impose a significant economic burden on this Brazilian tertiary public hospital, mainly related to bed cost per day and intensive care needs in young infants. These findings highlight the need for cost-effective RSV management and prevention strategies in Brazil.